Nonlinear Ion-Acoustic Waves in Degenerate Plasma with Landau Quantized Trapped Electrons - Jahangir, R.; Ali, S. (Frontiers in Physics, 2021)
The formation of nonlinear ion-acoustic waves is studied in a degenerate magnetoplasma accounting for quantized and trapped electrons. Relying on the reductive perturbation technique (RPT), a three-dimensional Zakharov Kuznetsov (ZK) equation is derived, admitting a solitary wave solution with modified amplitude and width parameters. The stability of the ZK equation is also discussed using the k-expansion method. Subsequently, numerical analyses are carried out for plasma parameters of dense stellar system involving white dwarf stars. It has been observed that quantized magnetic field parameter η and degeneracy of electrons (determined by small temperature values T) affect the amplitude and width of the electric potential. The critical point at which the nature of solitary structure changes from compressive to rarefactive is evaluated. Importantly, the growth rate of the instability associated with a three-dimensional ZK equation depends on the plasma parameters and higher values of η and T tend to stabilize the solitons in quantized degenerate plasmas. The results of present study may hold significance to comprehend the properties of wave propagation and instability growth in stellar and laboratory dense plasmas.